DETERMINANTS OF NATIONAL HEALTH INSURANCE RETENTION AMONG INFORMAL WORKERS IN PHNOM PENH, CAMBODIA (Proceedings of the Global Public Health Conference, 2025)
This study aimed to investigate the determinants of Retention in National Health Insurance (NHI) in Cambodia, among the informal workers in Phnom Penh, Cambodia. Surveys of 424 informal workers in Phnom Penh from September to October 2024 were conducted. Multivariate logistic regression analyses were performed to assess the factors associated with NHI retention among the informal workers. The results revealed that having completed secondary school or higher, working in industrial or service sectors, perceiving high technical and interpersonal quality of healthcare, perceiving comprehensive benefit coverage, and perceiving good availability of healthcare services were significantly associated with retention in the NHI scheme. Additionally, participants with a good level of knowledge about the benefit package were more likely to maintain active membership. It was concluded that while socio-economic and accessibility factors play a critical role, motivational and ability-related factors, such as knowledge of benefit packages, positive perceptions of service quality, and attitudes toward coverage, substantially influence informal workers’ decision to remain enrolled in the scheme. Improving awareness of benefit entitlements and promoting the technical and interpersonal aspects of healthcare quality through targeted health education interventions may enhance NHI retention among informal workers.
Keywords: Cambodia; informal workers; national health insurance; retention; universal health coverage; social health insurance